Didactics of the symbol in the practice of school education - Dagmara Ratajczak-Parzyńska (Studia z Teorii Wychowania)
The purpose of this text is to present a specific view on didactics, its theories and practical perspectives. The author intends to show theoretical considerations describing the issue of the symbol in teaching in the scope of educational tasks in a contemporary school. The implementation of this aim requires the reconstruction of the basic determinants of the symbol itself and its ontological approach to the didactics of the symbol. I am convinced that the symbol can become a category of humanistic theory for general education, showing its implementation capabilities.